Analisis Kinerja Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Masa Pandemi Covid-19 - Ni Made Ratna Puspita Dewi; I Putu Fery Karyada; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2023)
This study aims to investigate whether there are differences in the company's financial performance before and during the Covid-19 Pandemic and to find out the strategies taken by the company to survive during the Covid-19 Pandemic. This research was conducted at food and beverage industry sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2018-2020. The results showed that financial performance based on the current ratio had an average growth rate of 0.24 which means the company experienced an increase in liquidity even though it was affected by the pandemic. The average growth based on the debt to equity ratio is 30.22%, where the low ratio indicates that the company's debt is smaller than the amount of its assets. While the growth based on total asset turnover is -0.24, this explains that the assets owned by the company cannot be used to make a profit, which means that the company is currently experiencing difficulties in using all of its assets to generate sales. Based on the return on assets, the average growth is 0.24 this means that the company's management has not been able to use assets to generate maximum income